Airway Hyperresponsiveness in Asthma Model Occurs Independently of Secretion of β1 Integrins in Airway Wall and Focal Adhesions Proteins Down Regulation. Issue 10 (4th April 2016) - Álvarez‐Santos, Mayra; Carbajal, Verónica; Tellez‐Jiménez, Olivia; Martínez‐Cordero, Erasmo; Ruiz, Victor; Hernández‐Pando, Rogelio; Lascurain, Ricardo; Santibañez‐Salgado, Alfredo; Bazan‐Perkins, Blanca
ABSTRACT: The extracellular domains of some membrane proteins can be shed from the cell. A similar phenomenon occurs with β1 integrins (α1β1 and α2β1) in guinea pig. The putative role of β1 integrin subunit alterations due to shedding in airway smooth muscle (ASM) in an allergic asthma model was evaluated. Guinea pigs were sensitized and challenged with antigen. Antigenic challenges induced bronchoobstruction and hyperresponsiveness at the third antigenic challenge. Immunohistochemistry and immunoelectronmicroscopy studies showed that the cytosolic and extracellular domains of the β1 integrin subunit shared the same distribution in airway structures in both groups. Various polypeptides with similar molecular weights were detected with both the cytosolic and extracellular β1 integrin subunit antibodies in isolated airway myocytes and the connective tissue that surrounds the ASM bundle. Flow cytometry and Western blot studies showed that the expression of cytosolic and extracellular β1 integrin subunit domains in ASM was similar between groups. An increment of ITGB1 mRNA in ASM was observed in the asthma model group. RACE‐PCR of ITGB1 in ASM did not show splicing variants. The expression levels of integrin‐linked kinase (ILK) and paxillin diminished in the asthma model, but not talin. The levels of phosphorylation of myosin phosphatase target subunit 1 (MYPT1) at Thr 696 increased in asthma model. Our work suggests that β1 integrin is secreted in guinea pig airway wall. This secretion is not altered in asthma model; nevertheless, β1 integrin cytodomain assembly proteins in focal cell adhesions in which ILK and paxillin are involved are altered in asthma model. J. Cell. Biochem. 117: 2385–2396, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The extracellular domains of some membrane proteins can be shed from the cell. We found that β1 integrin is not only shedded but also secreted in airway wall. This secretion is not altered in asthma model; nevertheless, focal adhesions assembly is modify in asthma.